Influence of clonazepam on epileptic after-discharges induced by perforant path stimulation in rats - Kubová, H; Mares, P (Archives internationales de pharmacodynamie et de therapie, 1989)
The action of clonazepam (CZP) against after-discharges (ADs) induced by perforant path stimulation was studied in 11 rats with implanted electrodes. The animals passed 4 sessions: one control, one with the solvent injection, and two with the administration of CZP (either 0.1 or 1 mg/kg i.p.). The ADs were always induced 4 times with 20 min intervals, the injections took place 10 min before the second stimulation. The EEG pattern of ADs was not changed by either dose of CZP and the duration was transiently shortened by the high dose only. Incidence of recurrent ADs tended to decrease after the lower dose of CZP, the higher dose blocked them for at least 30 min. As concerns behavioral concomitants of ADs, wet dog shakes remained uninfluenced by CZP while orienting reaction was either fully blocked (by the high dose of CZP) or significantly suppressed (by the lower dose).
Keywords: Behavior, Animal; Electroencephalography; Male; Rats, Inbred Strains; klonazepam; elektrická stimulace; Solvents; rozpouštědla; elektroencefalografie; Electric Stimulation; mužské pohlaví; inbrední kmeny potkanů; Neural Pathways; Limbic System; epilepsie; krysa rodu Rattus; limbický systém; Animals; zvířata; Rats; nervové dráhy; chování zvířat; Clonazepam; Epilepsy